The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.fsigen.2019.102204
|View full text |Cite
|
Sign up to set email alerts
|

Ysurnames? The patrilineal Y-chromosome and surname correlation for DNA kinship research

Abstract: The Y-chromosome is a widely studied and useful small part of the genome providing different applications for interdisciplinary research. In many (Western) societies, the Y-chromosome and surnames are paternally coinherited, suggesting a corresponding Y-haplotype for every namesake. While it has already been observed that this correlation may be disrupted by a false-paternity event, adoption, anonymous sperm donor or the cofounding of surnames, extensive information on the strength of the surname match frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…17 Y-STRs targeted by the CSYseq are also present in the commercial kits developed for MPS (ForenSeq and PowerSeq): DYS19 , DYS389I/II , DYS390 , DYS391 , DYS392 , DYS448 , DYS456 , DYS460 , DYS522 , DYS533 , DYS549 , DYS570 , DYS612 , DYS635 , DYS643 and Y-GATA-H4 . As an internal control, 21 Y-STR loci sequenced by the CSYseq were compared to previously obtained PCR-CE results from our in-house YForGen kit (46 Y-STRs) and commercial Y-kits [ 44 ]. We observed that all Y-STR allele calls were in accordance with our previous results, which confirms that the results of MPS are reliable.…”
Section: Resultsmentioning
confidence: 99%
“…17 Y-STRs targeted by the CSYseq are also present in the commercial kits developed for MPS (ForenSeq and PowerSeq): DYS19 , DYS389I/II , DYS390 , DYS391 , DYS392 , DYS448 , DYS456 , DYS460 , DYS522 , DYS533 , DYS549 , DYS570 , DYS612 , DYS635 , DYS643 and Y-GATA-H4 . As an internal control, 21 Y-STR loci sequenced by the CSYseq were compared to previously obtained PCR-CE results from our in-house YForGen kit (46 Y-STRs) and commercial Y-kits [ 44 ]. We observed that all Y-STR allele calls were in accordance with our previous results, which confirms that the results of MPS are reliable.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the lack of recombination and the relatively low mutation rate (~10 −3 mutations per marker per meiosis) of the Y-STRs typically used in forensic Y-chromosome analysis, a Y-STR haplotype highlights the male perpetrator together with many of his paternally related male relatives. This allows particular forensic Y-STR applications of genetic identification such as familial searching (Kayser, 2017), forensic genealogy (Phillips, 2018), or surname prediction (Claerhout et al, 2020). In general, however, forensic DNA analysis seeks individual identification.…”
Section: Introductionmentioning
confidence: 99%
“…Other populations with low genetic diversity values when compared to the present results include those from Croatia (R st =0.0077, P=0.0148, Grskovic et al, 2011 ), Slovenia (R st =0.0497, P=0.0000, Sterlinko et al, 2001), Hungary (R st =0.0806, P=0.0000, Füredi et al, 1999;Egyed et al, 2000;Beer et al, 2004;Völgyi et al, 2009;Pamjav et al, 2017), Greece (R st =0.0943, P=0.0000, Parreira et al, 2002;Robino et al, 2004;Bosch et al, 2006;Kovatsi et al, 2009;Katsaloulis et al, 2013;Martínez et al, 2016) and North Macedonia (R st =0.1000, P=0.0000, Spiroski et al, 2005;Jakovski et al, 2019;Jankova et al, 2019). The highest genetic distance was observed when our study population was compared with the populations of Belgium (R st = 0.2341, P=0.000, Roewer et al, 2001;Maesschalck et al, 2005;Mertens et al, 2007;Purps et al, 2014;Claerhout et al, 2020), Italy (R st =0.2133, P=0.0000, Grignani et al, 2000;Presciuttini et al, 2001;Ghiani et al, 2002;Cerri et al, 2005;Robino et al, 2006;Turrina et al, 2006;Onofri et al, 2007;Ferri et al, 2008;Ferri et al, 2009;Rodríguez et al, 2009;Verzeletti et al, 2009;Brisighelli et al, 2012;Piglionica et al, 2013;Robino et al, 2015;Rapone et al, 2016;Sarno et al, 2016;…”
Section: Resultsmentioning
confidence: 61%
“…Genetic distances were used to produce MDS plots for the comparison of population haplotype data, which were automatically generated on YHRD using the data available in this database. European populations selected for comparison with the population of B&H include: B&H (n = 480, present study), previously published data for the general Bosnian-Herzegovinian population (n = 100, Kovacevic et al, 2013), Croatia (n = 232, Grskovic et al, 2011), Slovenia (n = 97, Sterlinko et al, 2001, Belgium (n = 708, Roewer et al, 2001;Maesschalck et al, 2005;Mertens et al, 2007;Purps et al, 2014;Claerhout et al, 2020), Hungary (n = 576, Füredi et al, 1999Egyed et al, 2000;Beer et al, 2004;Völgyi et al, 2009;Pamjav et al, 2017), Austria (n =253, Berger et al, 2005;Roewer et al, 2005;Erhart et al, 2012;Niederstätter et al, 2016;Pickrahn et al, 2016), Germany (n = 2756, Junge et al, 1997;Lessig and Edelmann, 1998;Schneider et al, 1998;Anslinger et al, 2000;Hidding et al, 2000;Henke et al, 2001;Schmidt et al, 2003;Immel et al, 2005;Kayser et al, 2005;Hohoff et al, 2007;Rodig et al, 2007), Czech Republic (n = 109, Zastera et al, 2010), Greece (n = 242, Parreira et al, 2002;Robino et al, 2004;Bosch et al, 2006;Kovatsi et al, 2009;Katsaloulis et al, 2013;Martínez...…”
Section: Methodsmentioning
confidence: 99%